2016
DOI: 10.1111/ijfs.13292
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐induced changes in physical and functional properties of whey proteins

Abstract: Use of high-intensity ultrasound to modify certain functional properties of whey proteins is an alternative to traditional method in food industry. Whey protein isolate (WPI) solutions were treated with an ultrasound probe (20 kHz) at different intensities (20% or 30% amplitude) and durations (10 or 20 min). Results showed that ultrasound treatment changed physical and several functional properties of whey proteins including decreased particle size (from 190.4 nm to 138.0 nm), increased surface hydrophobicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 36 publications
10
36
0
2
Order By: Relevance
“…The sound waves resulting from the motion of continuous longitudinal waves when sound travels through a medium can generate the alternate compression and rarefaction of the particles in the medium and the consequent collapse of the bubbles causing cavitation (Patist & Bates, ). The cavitation produced by ultrasound can cause a rapid rise in temperature up to 5500 °C and increase the pressure up to 50 MPa (Patist & Bates, ) and is therefore used to accelerate mass transfer, break down and dislodge particles, destroy the cell membrane or even change the structure of compounds(Kentish & Feng, ; Shen et al ., ).…”
Section: Nonthermal Processing Technologiesmentioning
confidence: 97%
See 1 more Smart Citation
“…The sound waves resulting from the motion of continuous longitudinal waves when sound travels through a medium can generate the alternate compression and rarefaction of the particles in the medium and the consequent collapse of the bubbles causing cavitation (Patist & Bates, ). The cavitation produced by ultrasound can cause a rapid rise in temperature up to 5500 °C and increase the pressure up to 50 MPa (Patist & Bates, ) and is therefore used to accelerate mass transfer, break down and dislodge particles, destroy the cell membrane or even change the structure of compounds(Kentish & Feng, ; Shen et al ., ).…”
Section: Nonthermal Processing Technologiesmentioning
confidence: 97%
“…() reported that porcine cerebra hydrolysates treated by ultrasound for 2 s (20 kHz, 0.32 W cm −2 ) can increase the content of peptides and hydrophilic and late‐eluting hydrophobic peptides and increase their radical scavenging activity and iron chelating activity. Similar results have been observed in wheat gluten, whey proteins and other food proteins treated by ultrasound technology (Arzeni et al ., ; Stefanović et al ., ; Shen et al ., ). These results indicate that the ultrasound can promote protein hydrolysis, while the effect or degree of hydrolysis is related to the energy, frequency and treatment time of ultrasound (Ozuna et al ., ).…”
Section: Nonthermal Processing Technologiesmentioning
confidence: 97%
“…This technique has been widely used for the processing of liquid-liquid or liquid-solid samples. However, the efficiency of this technique is influenced by several factors such as pressure, temperature, frequency as well as time of sonication (Kentish and Feng 2014;Shen et al 2017). Amidst all, frequency is one of the major factors that have a profound effect not only on the yield, but also on the properties of the compound.…”
Section: Ultrasound-assisted Extractionmentioning
confidence: 99%
“…Amidst all, frequency is one of the major factors that have a profound effect not only on the yield, but also on the properties of the compound. It has been reported that extraction using more than 20 kHz energy affected the physico-chemical properties of the phytochemicals with the formation of free radicals (Shen et al 2017;Kentish and Feng 2014).…”
Section: Ultrasound-assisted Extractionmentioning
confidence: 99%
“…The solubility of β-lactoglobulin was measured at pH 7 according to the method with some modifications (Shen, Shao, & Guo, 2016). All samples were lyophilized by freeze-drying at 0.034 mbar for 24 hr (Christ, Alpha 1-2 LDplus, Germany).…”
Section: Determinationofsolubilitymentioning
confidence: 99%